A blockchain‐enabled secured fault allocation in smart grids based on μPMUs and UT. Issue 16 (18th November 2021) - Almutairi, Abdulaziz; Alrumayh, Omar; Alyami, Saeed; Albagami, Naif; Hossein, Mohamed
Abstract: Improvements in the high accuracy of micro‐phasor measurement unit (μPMU) and synchrophasor unit provide the distribution network a special perspective to access full observability in the presence of renewable distribution generations (DGs). In this regard, modelling the uncertainty effects for accurate fault detection in smart grids has become a novel turning point. This research work attempts to develop a novel stochastic architecture based on unscented transform (UT), which requires a very few number of μPMUs, to communicate in a secured blockchain‐enabled structure to allocate and detect the smart grid irregularities and faults. Such a blockchain‐based technique can be beneficial for encrypting the data transmitted among the μPMUs in the smart grid consisting of a variety of distributed energy sources (DERs) and high impedance fault events, while incorporating the uncertainties associated with the load and individual installation sensors. The proposed stochastic structure benefits from voltage measurement and uses its angle in event placement that performs more efficiently than the conventional sensors based on high‐voltage and current metering. The simulation results show the great precision and effectiveness of the proposed model during various fault scenarios in smart grid.